Effects of burning on the aerial biomass dynamics of a native field in the Pantanal - Cardoso, Evaldo Luis; Crispim, Sandra Mara Araújo; Rodrigues, Cristina Aparecida Gonçalves; Júnior, Waldomiro Barioni (Pesquisa Agropecuaria Brasileira, 2003)
This work aimed to assess the effects of burning on the aerial biomass dynamics of aboveground herbaceous plants of a native field of the Pantanal presenting a dominance of Andropogon bicornis. The area under study was treated without burning (control) and with burning, both of them ungrazed. Aerial biomass and soil cover were analyzed during eleven months after burning. The aerial biomass in the with-burning area presented a short linear increment of dry matter. This biomass was expressively shorter than that biomass produced in the without-burning area. Andropogon bicornis, Axonopus purpusii and other species presented less biomass after burning. However, Mesosetum chaseae benefited from burning, presenting higher dry matter production. Burning almost removed all of the vegetal cover and, thirty days after burning, soil cover was approximately 35%. Seven months after burning, vegetal cover was re-established and became similar to the area without burning.